Pengaruh Metode Pembelajaran Brainstorming Terhadap Kemampuan Berpikirkritis Materi Vertebrata Pada Siswa SMA - Dzaalika Aldeirre; Ratna Komala; Erna Heryanti (Florea : Jurnal Biologi dan Pembelajarannya, 2018)
Brainstorming Learning Method is one of the learning methods that help teachers to achieve the goals of the learning process. Critical thinking is a process for learners to digest first things that have been obtained by looking at from other sources then can create their own conclusions. One of learning that requires critical thinking is Vertebrate subject matter. This study aims to determine the effect of brainstorming learning method on critical thinking of Vertebrate subject matter in high school students. This research was conducted in SMA Negeri 31 Jakarta. The number of research samples were 132 students using Taro Yamane formula selected by simple random sampling. This research was conducted in May-June 2018. The research method used is quasi- experimental method. The result of the research is the average score of critical thinking ability test of Vertebrata subject matter in experiment classis higher than the average score of critical thinking ability test of Vertebrate material in control class, prerequisite test shows normal and homogenous distribution data. Testing statistical hypothesis based on calculations that have been done, obtained p-value<α is 0,000<0.05 then. The conclusion of this research is the influence of brainstorming method on Vertebrate subject matter critical thinking ability in high school students.